Preservasi Digital Warisan Budaya: Sebuah Ulasan - Dwi Putra, Dedy; Sahrul Bahtiar, Firma; Nizam Rifqi, Ach.; Mardiyanto, Verry (Universitas Sebelas Maret Library, 2023)
Digital preservation plays an important role in safeguarding cultural heritage. Along with the development of the times, cultural heritage as a valuableassetcannot be separated from potential threats in the form of damage and loss. Digital preservation is an aspect of opportunity in maintaining the sustainability of cultural heritage values. Through a qualitative approach with the literature study method, this research seeks to provide an overview of aspects of digital preservation in relation to efforts to protect cultural heritage. The results of the study illustrate that digital preservation has strong relevance in terms of protecting cultural heritage values from damage and loss. The involvement of technology in digital preservation results in convenience in efforts to save cultural heritage by representing cultural material in digital formats. Digital preservation has various challenges including technological obsolescence, loss or damage to data, intellectual property rights, preservation costs, metadata and contextual information, skills and expertise, social and ethical considerations, utilization, and various other things according to the context of implementation. A digital preservation strategy that includes aspects of technological environmental conservation for future use and handling of technical limitations is an integral part of overcoming existing challenges. By implementing various strategies and actively participating in the realm of digital preservation activities, the existence of cultural heritage with its noble values can be maintained and gain long-term accessibility for the sustainability of future generations.